2002
DOI: 10.1046/j.1365-2664.2002.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Using ants as bioindicators in land management: simplifying assessment of ant community responses

Abstract: Summary1. The indicator qualities of terrestrial invertebrates are widely recognized in the context of detecting ecological change associated with human land-use. However, the use of terrestrial invertebrates as bioindicators remains more a topic of scientific discourse than a part of land-management practice, largely because their inordinate numbers, taxonomic challenges and general unfamiliarity make invertebrates too intimidating for most land-management agencies. Terrestrial invertebrates will not be widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
153
1
23

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(178 citation statements)
references
References 39 publications
1
153
1
23
Order By: Relevance
“…It is the dominant ant taxon of the New World ground assemblages and has been highlighted as an ideal focal group for the assessment of local ant biodiversity (Wilson 2003). The strong negative responses of Pheidole species to forest modification indicates that the genus should be also evaluated as a surrogate for assessment of ant community responses to habitat modifi cation, in the context of simplifying the protocol in studies on ecological change associated with human land-use (Andersen et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the dominant ant taxon of the New World ground assemblages and has been highlighted as an ideal focal group for the assessment of local ant biodiversity (Wilson 2003). The strong negative responses of Pheidole species to forest modification indicates that the genus should be also evaluated as a surrogate for assessment of ant community responses to habitat modifi cation, in the context of simplifying the protocol in studies on ecological change associated with human land-use (Andersen et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ants are commonly used as a focal group of insect biodiversity studies (Wolters et al 2006) and environmental monitoring work (Andersen et al 2004, Hoffmann & Andersen 2003, Yves et al 2004, because they are ubiquitous, diverse and abundant (Wilson & Hölldobler 2005), sensitive to habitat changes (Andersen et al 2002), have a straightforward taxonomy , and because of the general ease with which they can be studied , Philpott & Armbrecht 2006. This study describes the results of an analysis of the leaflitter ant fauna found in an area reforested with Pinus elliottii in relation to an adjacent relatively old undisturbed secondary Atlantic Forest, both localized in southeastern Brazil.…”
mentioning
confidence: 99%
“…Besides the high abundance, ants are a diverse group, with more than 12,500 described species (Antbase.org, 2009). Ants have also been widely used as bioindicators in land management (Andersen et al, 2002), because of their roles as seed dispersers (Hughes (Dyer & Letourneau, 1999), and ecosystems engineers (Folgarait, 1998). The use of ants or other organisms as bioindicators is more useful when supported by relationships with environment changes at spatial scales relevant to the management of biological reserves.…”
Section: Introductionmentioning
confidence: 99%
“…As variáveis biológicas e químicas altamente correlacionadas entre si foram: Formicidae e Araneae; Chilopoda e capacidade de troca de cátions; Enchytraeidae e manganês. Formigas e aranhas podem ser consideradas sensíveis às práticas de manejo, sendo que a utilização de práticas inadequadas refletem na comunidade de aranhas (ANDERSEN et al, 2002), porém, nesta pesquisa, estes grupos apresentaram uma baixa densidade. A presença de formigas pode refletir na fase de recuperação do solo, com uma variabilidade de hábitos alimentares e vivendo em agregados com alta densidade (ANDERSEN et al, 2002).…”
unclassified